Giant strides : an authoritative account of the transformational achievements of the PDP led administration of President Olusegun Obasanjo 1999-2007 - Ubani, Anthony (Nigeria: Genuine Bookplace Resources, 2006)
Presented in two impressive volumes, Giant Strides is a one stop encyclopedia on the sterling reforms and transformational achievements of President Olusegun Obasanjo in office. The book provides a refreshing incisive, in-depth and insightful account of the various programs, policies and interventions that moved Nigeria from backwardness and pariah status to international respectability, socio-political stability and outstanding economic progress and development in less than seven years.
with a foreword written by the National Chairman, peoples democratic party (PDP) his excellency, senator Dr. Ahmadu Ali, GCON
includes index.
rpm 03/09/13
Ref.
Keywords: Nigeria; Public administration; Nigeria